2018
DOI: 10.1021/acsbiomaterials.8b01363
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Single-Carbon-Dot Transmembrane Transport by Force Tracing Based on Atomic Force Microscopy

Abstract: Carbon dots (CDs) evoke a great deal of attention in biomedicine because of their unique properties. As an emerging theranostic agent, the CDs transmembrane transport process is the first and the most important step. Herein, a transmembrane dynamic process of transporting single CDs with folic acid into normal cells (Vero) and cancer cells (HeLa) were tracked by means of a force tracing technique based on atomic force microscopy. Meanwhile, the kinetic parameters of the the transmembrane process were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Subsequently, the AFM tip was slowly moved to the contact point and slightly brought into contact with the cell surface via the AFM feedback system, and then the feedback system was turned off. 12 The diagram of the force tracing setup is shown in Figure 1B, the photodetector will record the change of laser position caused by the cantilever deflection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the AFM tip was slowly moved to the contact point and slightly brought into contact with the cell surface via the AFM feedback system, and then the feedback system was turned off. 12 The diagram of the force tracing setup is shown in Figure 1B, the photodetector will record the change of laser position caused by the cantilever deflection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Taking the advantages of high temporal− spatial resolution and single-particle tracking under physiological conditions, the force tracing technique on the basis of atomic force microscopy (AFM) has proven to be an excellent method for studying the transmembrane dynamic mechanism. 12 Force tracing could detect force as low as 10 pN and track fast processes down to 10 μs, which is much faster than other force testing techniques (for example, magnetic forceps, 13 optical tweezers, 14 and glass microneedles 15 ). The force tracing technique has been used to study the differences in transmembrane transporting dynamic parameters of gold nanoparticles (Au NPs, 5 nm, 10 nm, and 20 nm).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the size control method of most colloidal materials is mature nowadays, and sub-30-nm-sized NPs, including UCNPs (Liu et al, 2017;Zhan et al, 2017), SiNPs (Liang et al, 2020), AIE dots (Fang et al, 2017;Li et al, 2017;Li et al, 2018), PDots (Wu et al, 2020), and QDots (Lesoine et al, 2013;Hanne et al, 2015;Ye et al, 2018;Zhao et al, 2019), have all been successfully fabricated for STED applications, some of which are even commercially available (Hanne et al, 2015;Zhao et al, 2019). CDots (Leménager et al, 2014;Wang et al, 2017;Han et al, 2019;Hua et al, 2019;Li et al, 2019), on the contrary, are naturally nano-sized (<10 nm) and are well known for their fast transport dynamics across membranes (Lu et al, 2019). For FNDs and LPR nanohybrid particles, the smallest particle size in reported STED imaging cases is 40∼50 nm (Tzeng et al, 2011;Urban et al, 2018).…”
Section: Particle Sizementioning
confidence: 99%
“…3d), which may be attributed to the larger molecule structure of EGF and the more complex EGF–EGFR receptor-mediated endocytosis. 25 However, the probability of an observed force–time signal is lower (6.9%) than that of PAMAM-CPT-EGF (13.6%), indicating the higher transporting efficiency of PAMAM-CPT-EGF. Likewise, Wei-Ting Kuo et al also concluded that EGF has a higher adhesion force and binding affinity to EGFR.…”
mentioning
confidence: 93%